Develop the constructionpreneurial business success checklist in the construction industry - Zahidy, Abd Hamid (2016)
Earlier conceptions of success in the construction industry placed a great emphasis on the project-based success criteria. Emphasising on this criterion has led to the vast efforts paid to grandiose the theory on project-based management practices to improve the efficiency of individual projects. Yet, success still proves to be elusive in many construction companies, which recorded the biggest percentage of failed businesses globally of 20.2%. In response to this issue, the objective of this study was to explore the success indicators for entrepreneurs in the construction industry from a different view, that is, from the perspectives of an entrepreneurship phenomenon. To guide the research effort, the overarching research question was formulated as: what are the success indicators for entrepreneurs in the construction industry? Following a review of existing knowledge in the entrepreneurship literature, a list of twenty three relevant indicators was proposed with a conceptual research model relies on four knowledge areas of an entrepreneurship phenomenon, namely entrepreneurial orientation, entrepreneurial organisation, entrepreneurial competency, and entrepreneurial environment. This research was conducted in two phases of research inquiry with the use of a mixed method research design. In the first phase, two rounds of the Delphi study was employed to identify the most important indicators to the success of construction enterprise. Then, the Decision Making and Trial Evaluation Laboratory (DEMATEL) was used to explore the interrelationships among those importance indicators in the second phase. The data was solicited from a panel of thirty nine construction industry experts comprising of contractor/developer, professional engineering consultant, government technical officer and academician, and was applicable for both phases. The Cronbach's alpha coefficient for the Delphi study and DEMATEL technique were 0.827 and 0.768, respectively, which implied high reliability of the instruments. The questionnaires were electronically transmitted to the expert panellists with the response rates of 100% in the first round and 92.3% in the second round of the Delphi study, and 55.6% in the DEMATEL technique. The overall research findings revealed that eighteen indicators were of importance with three indicators was the most critical and driving indicators to the success of the construction enterprise. In addition, a checklist named the Constructionpreneurial Business Success Checklist was developed and validated. The validation tests indicated that this checklist could be an appropriate tool for guiding the construction enterprise in monitoring their business toward an achievement of the long-term corporate success, and beneficial for the intended users. This research is expected to generate a new knowledge in the CEM literature as it highlights the benefits of the entrepreneurial activities brought to the successful business in the construction industry. Nevertheless, a list of practical implementation of success indicators forwarded by the research is expected to be applicable to a various stakeholders within the construction industry. From a research perspective, the study could stimulate further interest in the CEM and entrepreneurship research.